Doença periodontal materna como fator associado ao baixo peso ao nascer Maternal periodontal disease as a factor associated with low birth weight - Simone Seixas da Cruz; Maria da Conceição N Costa; Isaac Suzart Gomes Filho; Maria Isabel P Vianna; Carlos Teles Santos (Universidade de São Paulo, 2005)
OBJETIVO: Estudos recentes têm apresentado evidências de que a doença periodontal em gestantes pode ser um dos determinantes do baixo peso ao nascer. Realizou-se estudo para verificar a existência de associação entre doença periodontal materna e baixo peso ao nascer. MÉTODOS: Estudo do tipo caso-controle com 302 mulheres, sendo 102 mães de nascidos vivos de baixo peso (grupo caso) e 200 mães de nascidos vivos com peso normal (grupo controle). A existência de associação entre doença periodontal e baixo peso ao nascer foi avaliada mediante modelo multivariado de regressão logística, considerando outros fatores de risco para o baixo peso. RESULTADOS: Ambos os grupos de mães eram comparáveis no que se refere a idade, altura, peso pré-gestacional, tabagismo, alcoolismo, doenças prévias, estado civil, situação socioeconômica, número de escovações e uso de fio dental, número de refeições diárias, e visitas ao dentista. A doença periodontal foi diagnosticada em 57,8% das mães do grupo caso e 39,0% do grupo controle. A análise de regressão logística indicou associação positiva entre doença periodontal e baixo peso ao nascer (ORbruto=2,15; IC 95%: 1,32-3,48), especialmente entre as mães com escolaridade menor ou igual a quatro anos (ORajustada=3,98; IC 95%: 1,58-10,10). CONCLUSÕES: A doença periodontal é um possível fator de risco para o baixo peso ao nascer. OBJECTIVE: Recent studies have presented evidence that periodontal disease in pregnant women may be a determining factor for low birth weight. The present investigation was carried out to verify whether or not there is an association between maternal periodontal disease and low birth weight. METHODS: This was a case-control study on 302 women, of whom 102 were the mothers of live newborns of low weight (case group) and 200 were the mothers of live newborns of normal birth weight (control group). The existence of an association between periodontal disease and low birth weight was evaluated by means of a multivariate logistic regression model that considered other risk factors for low weight. RESULTS: The two groups were comparable with regard to age, height, pre-gestational weight, smoking, alcohol use, previous diseases, marital status, socioeconomic status, frequency of tooth-brushing and use of dental floss, number of meals per day and visits to the dentist. Periodontal disease was diagnosed in 57.8% of the mothers in the case group and 39.0% in the control group. Logistic regression analysis indicated a positive association between periodontal disease and low birth weight (unadjusted OR=2.15; 95% CI: 1.32-3.48), especially among the mothers with schooling of less than or equal to four years (ORadjusted=3.98; 95% CI: 1.58-10.10). CONCLUSIONS: Periodontal disease is a possible risk factor for low birth weight.